The Dynamic Immune Response of Yellow Catfish (Pelteobagrus fulvidraco) Infected With Edwardsiella ictaluri Presenting the Inflammation Process - Zhou, Xu; Zhang, Gui-Rong; Ji, Wei; Shi, Ze-Chao; Ma, Xu-Fa; Luo, Zun-Lan; Wei, Kai-Jian (Frontiers in Immunology, 2021)
Edwardsiella ictaluri is a highly destructive pathogen in cultured yellow catfish, thus it was very necessary to study the immune response of yellow catfish against bacterial infection. In this study, RNA-Seq technology was used to study the immune response in two distinct tissues of yellow catfish at eight different time points (h) after E. ictaluri infection. The number of differentially expressed genes (DEGs) in the spleen and liver was low at 3 h and 6 h post-infection, respectively. Afterwards, the most number of DEGs in the spleen was detected at 72 h, while the number of DEGs in the liver maintained a high level from 24 h to 120 h. The GO and KEGG enrichment analyses of DEGs at different time points uncovered that cytokines were continuously transcribed at 6 h to 120 h; whereas the liver is the main organ that secretes the components of the complement system, and metabolic regulation was activated from 12 h to 120 h. Moreover, an overview of the inflammation response of yellow catfish was exhibited including pattern-recognition receptors, inflammatory cytokines, chemokines, complements, and inflammation-related signal pathways. The similar expression tendency of nine genes by qRT-PCR validated the accuracy of transcriptome analyses. The different transcriptomic profiles obtained from the spleen and liver will help to better understand the dynamic immune response of fish against bacterial infection, and will provide basic information for establishing effective measures to prevent and control diseases in fish.